Identification of Candida parapsilosis Sensu Lato in Pediatric Patients and Antifungal Susceptibility Testing - Cattana, Maria Emilia (2017)
A total of 59 Candida parapsilosis sensu stricto and 1 Candida orthopsilosis recovered from catheters and blood cultures of pediatric patients from the northeastern region of Argentina were studied. Susceptibility to azoles, amphotericin B, and echinocandins was tested by the broth microdilution method. According to CLSI clinical breakpoints, >91% of the strains were azole susceptible, whereas 15% showed high amphotericin B MICs.